A Titanium‐Doped SiOx Passivation Layer for Greatly Enhanced Performance of a Hematite‐Based Photoelectrochemical System. (30th June 2016) - Ahn, Hyo‐Jin; Yoon, Ki‐Yong; Kwak, Myung‐Jun; Jang, Ji‐Hyun
Abstract: This study introduces an in situ fabrication of nanoporous hematite with a Ti‐doped SiO x passivation layer for a high‐performance water‐splitting system. The nanoporous hematite with a Ti‐doped SiO x layer (Ti‐(SiO x /np‐Fe2 O3 )) has a photocurrent density of 2.44 mA cm −2 at 1.23 VRHE and 3.70 mA cm −2 at 1.50 VRHE . When a cobalt phosphate co‐catalyst was applied to Ti‐(SiO x /np‐Fe2 O3 ), the photocurrent density reached 3.19 mA cm −2 at 1.23 VRHE with stability, which shows great potential of the use of the Ti‐doped SiO x layer with a synergistic effect of decreased charge recombination, the increased number of active sites, and the reduced hole‐diffusion pathway from the hematite to the electrolyte.